A perpendicular bisector is a segment which intersects another segment on its midpoint and with a right angle.
First, we have to find the midpoint between X(-9,1) and Y(3,5), as follows
![\begin{gathered} M=((-9+3)/(2),(1+5)/(2)) \\ M=((-6)/(2),(6)/(2)) \\ M=(-3,3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/34bkbu04thg3bejbson0qgeeekuxwu63ps.png)
This means the perpendicular bisector must pass through (-3,3). Now, with the given points we find the slope of XY
![\begin{gathered} m=(y_2-y_1)/(x_2-x_1) \\ m=(5-1)/(3-(-9))=(4)/(3+9)=(4)/(12) \\ m=(1)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/csg7tzcyx951podmbp7g0pxfyhmdcnnf23.png)
Then, we apply the rule of perpendicularity to find the slope of the perpendicular bisector.
![\begin{gathered} m_1\cdot m=-1 \\ m_1=(-1)/(m) \\ m_1=-(1)/((1)/(3))=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/f1jjyay0dk5u3k1mrq33xbgn2eluwbpezh.png)
Now, we use the slope-point formula to find the equation for the perpendicular bisector.
![y-y_1=m(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/csobd57zth7rh9k4hz9amldzpq2owf0z4j.png)
Where we replace the slope -3 and the point (-3,3).
![\begin{gathered} y-3=-3(x-(-3)) \\ y-3=-3x-9 \\ y=-3x-9+3 \\ y=-3x-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yudq8nv2ragcrapobkfjyo5kpj0k4ymy8u.png)
Therefore, the right answer is C.